(untitled) (Research, Society and Development, 2021)
Objective: to evaluate the epidemiological aspects of Specific Hypertensive Syndrome of Pregnancy (SHEG), in Belém, Pará, during the period from January 2016 to December 2020. Methodology: epidemiological, retrospective and quantitative study whose data were obtained through information available at the Department Informatics of the Unified Health System (DATASUS). The following epidemiological variables were chosen: number of hospitalizations, years of hospitalization (2016 to 2020), age group, ethnicity (white, black, brown, yellow and without information) and number of deaths per year. Results: The study identified a total of 7386 cases of SHEG in the 5 years evaluated. Most of them occurred in patients aged 20 to 34 years (66.42%), 16.93% of patients with SHEG were adolescents (10 to 19 years) and 16.63% were aged 35 or over . Regarding the ethnicity of the research participants, there was a predominance of brown color (88.89%), followed by white (4.45%), black (1.81%) and yellow (0.06%), respectively. The study also identified a considerable number of deaths caused by SHEG. Conclusion: The present research showed the importance of health professionals, mainly from PHC, to always be aware of risk factors, in order to identify, in advance, those pregnant women with a higher risk of evolving to SHEG in order to guide them and provide more comprehensive and individualized prenatal care. In addition, improvements in the management of pregnant women in urgent and obstetric emergencies are imperative in order to reduce mortality associated with SHEG.